2023
DOI: 10.1007/s00268-023-07218-8
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Operative Intervention for Pediatric Burn Patients in Malawi

Dylane Davis,
Selena An,
Linda Kayange
et al.

Abstract: Background Defining the optimal timing of operative intervention for pediatric burn patients in a resource-limited environment is challenging. We sought to characterize the association between mortality and the timing of operative intervention at a burn center in Lilongwe, Malawi. Methods This is a retrospective analysis of burn patients (\18 years old) presenting to Kamuzu Central Hospital from 2011 to 2022. We compared patients who underwent excision and/or burn grafting based on the timing of the operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…
We commend Davis et al for their study regarding early excision for burn injury among children in Malawi [1]. The authors reviewed records of 2502 burn-injured children and found that the odds of mortality were higher for those who underwent excision within 72 h of injury compared to those who underwent excision later.
…”
mentioning
confidence: 99%
“…
We commend Davis et al for their study regarding early excision for burn injury among children in Malawi [1]. The authors reviewed records of 2502 burn-injured children and found that the odds of mortality were higher for those who underwent excision within 72 h of injury compared to those who underwent excision later.
…”
mentioning
confidence: 99%